Garden Watering Control System Using Solar Cells - Togar Timoteus Gultom; Suhelmi , Suhelmi (Journal of Resources and Reserves (JRR), 2024)
Watering the Garden by Using Solar Cells. Guided by Zahir Zainuddin and Adriani. Solar Cells are devices composed of semiconductor materials that can convert sunlight into electricity directly. Often also used the term photovoltaic or photovoltaic. In this design, the automatic garden watering using solar cells requires timer equipment, BCU, rain sensor, relay, battery/battery, and inverter. The purpose of this design is to know the performance of plant watering design by using solar cells as a source of stress and to know the control system and rain sensor in maximum watering of plants so that later can be applied to the next design and society. Garden Water Purification Test Using an Unsaturated Solar Cell on 31 December 2017 produced a Voltage of up to 18 volts with 1.5 ampere Current, and on 14 December 2017 made a Voltage of up to 17.5 volts with 1.4 ampere Flow. At the time, the load voltage issued by the battery of 11.5 V and issued a current of 5.73 A, and the voltage released by the inverter was 214 V and issued a current of 1.05 A. While the middle of the operation is also measured, the voltage is discharged by an 11.80 V battery with a current of 7.80 A and an output voltage of an inverter of 221 V and an output current of 0.81A.